Musical taste and the representativeness heuristic - Lonsdale, A.; North, Adrian (Sage Publications Ltd., 2011)
The present research investigated how people judge the musical taste of others. In Study 1, participants were asked to judge the likely musical taste of 10 fictional individuals. Participants’ judgements of musical taste exhibited a common bias in keeping with stereotypes of musical taste; this bias was believed to stem from the use of the representativeness heuristic. Study 2 confirmed this, showing that an individual’s similarity to stereotypical music fans, rather than base-rate estimates of musical taste, was significantly related to predictions of their likely musical taste. This suggests that an individual’s relative similarity to stereotypical music fans might act as a heuristic ‘rule of thumb’ used by people to quickly and economically judge their likely musical taste.